2018
DOI: 10.1097/qad.0000000000001760
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 treatment supports CD8+ mucosa-associated invariant T-cell restoration in HIV-1-infected patients on antiretroviral therapy

Abstract: : Chronic HIV-1 infection is associated with lower frequencies and functional impairment of mucosa-associated invariant T (MAIT) cells. We evaluated IL-7 treatment to restore MAIT cells in peripheral blood of chronically HIV-1 infected individuals on ART. IL-7 led to increased relative and absolute levels of MAIT cells and this expansion occurred primarily in the CD8+ subset. These results suggest that IL-7 may represent a therapeutic intervention for the restoration of MAIT cells in chronic HIV-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 9 publications
(19 reference statements)
2
24
0
Order By: Relevance
“…Treatment with cytokines during chronic SHIV infection showed that cytokine IL-7 might play a significant role in inducing MAIT cell frequencies in high levels. This is consistent with human data, which demonstrated that administration of IL-7 in vivo enhances the frequency and quality of MAIT cells during chronic HIV infection (49). These studies suggest that the IL-7 pathway could be modulated in vivo to augment the function of MAIT cells during chronic HIV infection.…”
Section: Discussionsupporting
confidence: 91%
“…Treatment with cytokines during chronic SHIV infection showed that cytokine IL-7 might play a significant role in inducing MAIT cell frequencies in high levels. This is consistent with human data, which demonstrated that administration of IL-7 in vivo enhances the frequency and quality of MAIT cells during chronic HIV infection (49). These studies suggest that the IL-7 pathway could be modulated in vivo to augment the function of MAIT cells during chronic HIV infection.…”
Section: Discussionsupporting
confidence: 91%
“…However, some human studies have described a functional impairment of MAIT cells in chronic HBV 68 and HIV 60,61 infection, with decreased IFNγ, TNF and IL-17A production and reduced cytotoxicity, after in vitro TCR-dependent activation, correlating with very low levels of expression of the transcription factors T-bet, EOMES, PLZF, RORγt and HELIOS 61 . In a small cohort of HIV-infected patients, treatment with recombinant human IL-7 restored the frequency of circulating MAIT cells, as was previously shown for conventional CD4 + and CD8 + T cells 64 , and functional analysis of one treated patient showed that MAIT cell responsiveness to IL-12 and/or IL-18 or E. coli stimulation was also restored 65 .…”
Section: Mr1-independent Activation Of Mait Cells Tcr-supporting
confidence: 73%
“…1). MAIT cells express high levels of IL-18 receptor (IL-18R) and IL-12R, and IL-18 and IL-12 have emerged as the major cytokines that activate MAIT cells upon bacterial or viral infection 43,45,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] ( TaBle 2). During bacterial infection, blockade or deletion of the IL-12p40 subunit impairs MAIT cell control of intracellular growth of F. tularensis and M. bovis 43,45 .…”
Section: Mr1-independent Activation Of Mait Cells Tcr-mentioning
confidence: 99%
“…This dysregulation of MAIT and iNKT cells was observed in some HIV-1-infected subjects who were on ART for over 15 years, suggesting that these cells do not recover even with viral suppression. Combination of ART with immunotherapies such as IL-7 and IL-2 has shown some capacity to increase MAIT and iNKT cell frequency ( 42 , 43 ). Altogether, our results suggest that HIV-1-associated defects in MAIT and iNKT cells could be in part responsible for the increased susceptibility of HIV-1-infected individuals to Mtb infection and more severe disease progression.…”
Section: Discussionmentioning
confidence: 99%